A role for the polarity complex and PI3 kinase in branch formation within retinotectal arbors of zebrafish. Issue 6 (9th December 2013) - Schmidt, John T.; Mariconda, Laura; Morillo, Francelina; Apraku, Elizabeth
ABSTRACT The developing zebrafish retinotectal arbors make many trial branches with synapses but most are retracted. With NMDA blockers, branches are withdrawn at a higher rate, and a synapse on a branch not only stabilizes that branch, but biases new branches to form nearby. Here, we tested whether new branch formation requires the polarity complex, which is essential for organizing the cytoskeleton in initial axon formation. The complex (PAR3, PAR6, and atypical protein kinase C [aPKC]) is downstream of phosphatidyl‐inositol‐3‐kinase (PI3K), and its aPKC could be activated by retrograde arachidonic acid synaptic signaling. DiO‐labeled arbors in zebrafish were imaged on day 3 (before treatment) and 1–2 days after treatment to suppress or inhibit PAR3, PAR6, or PI3K. Intraocular antisense (AS) oligos to PAR3 or PAR6 both severely limited branch addition, which was most evident in arbors with few branches before treatment. As a result of the inability to branch, arbor segments grew longer than in controls. Both PI3K inhibition (LY294002) and AS suppression of PI3Kα and PI3Kδ isoforms likewise limited branch addition but also decreased growth, as the sum of segment lengths was below normal after 2 days. Both the results support the idea that the polarity complex and PI3K participate in arbor branch formation. The PKC inhibitor Go6983 also severely restricted branch addition and growth, as did bisindolyl‐maleimide and calphostin C reported previously, consistent with PKCζ, but not PKCµ, participation. These experiments suggest a mechanism whereby activity signaling could affect the branching of retinotectal arbors. © 2013 Wiley Periodicals, Inc. Develop Neurobiol 74: 591–601, 2014